Un siècle d'étude de la mémoire : les hommes et les idées - Serge Nicolas (Les Cahiers de Framespa)
The history of scientific psychology of memory has been marked by two golden ages: the late nineteenth century and the late twentieth century. The article provides an overview of scientific psychological research on memory for more than a century. This presentation highlights the importance of major characters and major trends that have marked the history of research in this area.